Exploring Migration Motivations from Developed to Developing Countries: A Study of American Emigrants to Developing Countries - Mustafa Şeref Akın (Journal of Economy Culture and Society)
This paper explores the motivations and challenges faced by American emigrants by focusing on the stories of 12 individuals who moved to developing countries. Through an in-depth analysis of social media videos produced by the CNBC Make It program and the migrants, the study provides firsthand insights into their decision-making processes and the factors influencing their choices. Our findings reveal that economic opportunities are not the primary driver of early decision-making. Instead, motivations for migration are deeply rooted in social and psychological aspects, such as detachment from home communities and personal growth and fulfillment. Economic considerations, including the ability to earn income from the U.S. (through online work, retirement, or passive income), become relevant for geographic arbitrage only after the decision to migrate has been made. Having an income from home country, combined with the lower cost of living in developing countries, enables Americans to achieve financial independence. Notably, tax benefits are a low priority, contrary to popular belief about tax avoidance as a motivation. Therefore, migration from developed to developing countries is primarily a personal decision driven by a desire for change, adventure, creativity, and self-discovery.